Optimization Of Environmental Management And Community Empowerment Through The Role Of Village-Owned Enterprises And MSMES - Putu Kepramareni; Ni Luh Widyasari; Made Agung Raharja; Herry Putra Setiawan (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study aims to enhance the competencies of Village-Owned Enterprises (BUMDesa) and Farmer Business Groups in Sembung Gede Village. The main issues addressed include limited financial management skills, lack of knowledge in calculating production costs, insufficient use of technology in marketing, and inadequate waste management practices. Method: The research applies a community service approach through interviews, training sessions, coaching, and evaluations. These methods are designed to strengthen human resources in financial reporting, technology application, and environmental management. Practical Applications: The findings provide practical benefits by equipping local institutions with improved financial literacy, digital marketing skills, and sustainable waste practices, which can strengthen rural economies and support community welfare. Conclusion: The evaluation demonstrates an increase in the competencies of human resources, particularly in cost reporting, technology use, and waste sorting. This confirms that the training program effectively supports capacity building and sustainable community development.